PENGARUH SIZE, LEVERAGE, PROFITABILITY, CAPITAL INTENSITY RATIO DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE (ETR) - Ardyansah, Danis; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2014)
This study aims to examine the factors that affect the company’s effective tax rate. There are several factors used include size, leverage, profitability, capital intensity ratio and independent commissioners. The purpose of this study is to empirically examine whether the size, leverage, profitability, capital intensity ratio and independent commissioners affect the effective tax rate in manufacturing companies listed in Indonesia Stock Exchange.Population taken as the object of observation amounted to 148 manufacturing companies listed in Indonesia Stock Exchange in the periode 2010-2012. Determination of the sample was made by applying purposive sampling method and obtain a sample of 75 manufacturing companies based on certain cirteria.The results showed that the size and independent commissioners significant effect on the effective tax rate. While leverage, profitability and capital intensity ratio does not signifiacantly influence the effective tax rate. In this study, there are still many limitations and shortcomings namely the effect of independent variables on the dependent variable can only explain by 4.3%. Hence more independent variables are needed.